Injection of inactive Bordetella pertussis and complete Freund's adjuvant with Torpedo californica AChR increases the occurrence of experimental autoimmune myasthenia gravis in C57BL/6 mice - Takahiro Maruta; Minako Oshima; Dennis R. Mosier; M. Zouhair Atassi (Taylor & Francis Group, 2017)
An animal model of myasthenia gravis (MG), termed experimental autoimmune MG (EAMG), is an important tool for investigations of disease mechanisms and/or methods of treatment for this disease. EAMG can be induced in C57BL/6 (B6, H-2b) mice by 2-3 times injections at 4 weeks intervals with Torpedo californica (t) acetylcholine receptor (AChR) in complete Freund's adjuvant (CFA). However, the protocol especially with a two-injection schedule occasionally produces a poor incidence of EAMG. We have investigated the efficacy of the additional adjuvant, inactive organisms of Bordetella pertussis (iBP), on the induction with a two-injection schedule. In a group immunized with tAChR in CFA + iBP, 76% of mice developed EAMG (average grade in exercise test, 1.02). Whereas, 46% of mice were found EAMG-positive (average grade, 0.73) in a group injected with tAChR/CFA alone. Thus, the combined use of CFA and iBP significantly increased both the occurrence and severity of clinical MG in the immunized mice. This was accompanied by higher antibody (Ab) and T-cell responses to tAChR. The effect on disease occurrence of the iBP use in a three-injection protocol was also described.